The SNP rs13118928, rs1828591 and rs10519717 in the HHIP Gene are not Associated on COPD Susceptibility in Male Javanese Smokers - Syazili Mustofa; Sutyarso; Muhartono; Yandri; Retno Ariza Soeprihatini Soemarwoto; Hendri Busman; Wawan Abdullah Setiawan (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Hedgehog Interacting Protein (HHIP) gene polymorphisms have an association on COPDhas been carried out in Europe and Asia but in Indonesia there is still very limited study on this type andthe largest ethnic group in Indonesia is the Javanese. Objective: To analyze the association between theHHIP gene polymorphism and the incidence of COPD in male Javanese smokers in Lampung, Indonesia.Method: In a case-control study in Javanese male smokers, three single nucleotide polymorphism (SNPs)in the HHIP gene were analyzed by Sanger sequencing method. There were 110 participants in this studywhich were divided into 2 groups, such as COPD group (55 participants) and control group (55 participants).Three SNPs in the gene (rs13118928, rs1828591 and rs10519717) were selected for genotyping. Genotypedistributions were compared between patients and controls. The statistical analysis was carried out with theSPSS program with a chi-square test. Result: The genotypic frequency of the HHIP gene sequence at theSNP position rs1828591, such as AA (52.72%), GG (3.63%) and AG (43.63%) in COPD group, while inthe control group such as AA (38.18%), GG (9.09%) and GG (52.72%; p > 0.05). The genotypic frequencyof the HHIP gene sequence at the SNP position rs13118928 consisted of AA (47.27%) and AG (53.72%)in the control group, while the COPD group consisted of AA (52.72%), GG (1.81%) and AG (45.45%; p> 0.05). The genotypic frequency of the HHIP gene sequence at the SNP position rs10519717 consistedof TT (34.54%), CC (14.56%) and CT (50.90%) in COPD group, while controls group consisted of TT(23.63%), CC (16.37%) and CT (60.00%; p > 0.05). The genotypic analysis of Three SNPs in HHIP genewere observed but showed no significant difference between case and control groups. Conclusion: Singlenucleotidevariants in the HHIP gene are not associated with COPD susceptibility in Javanese male smokers.